Microemulsion-Based Delivery of Celery (Apium graveolens L.) Extract as a Hair Growth Promoter: Penghantaran Ekstrak Seledri (Apium graveolens L.) Berbasis Mikroemulsi sebagai Promotor Pertumbuhan Rambut - Wira Noviana Suhery; Nofriyanti; Nurul Latifah; Mustika Furi; Haiyul Fadhli; Rahayu Utami (JURNAL FARMASI DAN MAKANAN, 2025)
This study aimed to formulate a microemulsion of celery ethanol extract (Apium graveolens L.) and evaluate its physical properties and effects on rabbit hair growth. Four formulations were prepared: three containing celery extract at concentrations of 5% (FI), 7.5% (FII), and 10% (FIII), and one blank formula (F0). The microemulsions were assessed for organoleptic properties, percent transmittance, pH, density, viscosity, rheology, stability (including heating–cooling cycles and centrifugation), skin irritation, and globule size. Hair growth activity was tested in rabbits, and data were analyzed using two-way ANOVA. All formulations demonstrated good physical stability and caused no skin irritation. The results showed that the microemulsions significantly promoted hair growth, with the 10% extract formulation (FIII) showing the most pronounced effect, enhancing hair length by 2.7 times compared to the blank. These findings suggest that celery extract microemulsions, particularly at higher concentrations, are effective in stimulating hair growth.